2005
DOI: 10.1016/j.febslet.2005.07.095
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and inhibition of DNA transcriptional activity by spermine: A marked difference between linear and circular templates

Abstract: We compared the transcriptional activities of the circular and linear forms of short (4 kbp) and giant (106 kbp) DNA molecules in the presence of a polyamine, spermine (4+). With an increase in the spermine concentration, transcriptional activity was enhanced, followed by an inhibitory effect, and complete inhibition was observed in the sole case of long, linear templates. A difference between the transcriptional properties of circular and linear conformations is found for giant DNA molecules. These results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 23 publications
1
57
0
Order By: Relevance
“…DNA transcriptional activity:T he transcription and detection of RNA products was performed according to the procedure described by Luckel et al [13] In this assay,af luorescent analogue of UTP (i.e.,U TP g-AmNS) was used as one of the nucleotide substrates. Incorporation of uridine monophosphate (UMP) in RNA resulted in the release of g-AmNS, which has higher intrinsic fluorescence than UTP g-AmNS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA transcriptional activity:T he transcription and detection of RNA products was performed according to the procedure described by Luckel et al [13] In this assay,af luorescent analogue of UTP (i.e.,U TP g-AmNS) was used as one of the nucleotide substrates. Incorporation of uridine monophosphate (UMP) in RNA resulted in the release of g-AmNS, which has higher intrinsic fluorescence than UTP g-AmNS.…”
Section: Methodsmentioning
confidence: 99%
“…These concentrations are approximately 233-a nd 117-foldl ower than the concentrationo ft he conventional DNA-condensing agent spermine necessary to achieve the same effect (> 1400 mm). [13] Interestingly,t he concentration of the M enantiomer that resultsi nt he total inhibition of DNA transcription (6 mm)i se quivalent to aD NA base/ helicateratio of 5:1; therefore, it is indicated that the DNA condensation induced by M-[Fe 2 L 3 ]Cl 4 might interferew ith transcriptional activity.…”
Section: Inhibition Of Dna-transcriptionalactivitymentioning
confidence: 98%
See 1 more Smart Citation
“…From a physical point of view, a DNA molecule, which is longer than several lm (>100 kbp), shows the characteristics of a semiflexible polymer, which exhibits a discrete transition between coiled and compact states; i.e., first-order phase transition for a single giant DNA molecule under the criterion of Landau's symmetry argument [21,2]. It has also been reported that the transcriptional activity of a giant DNA molecule is switched on or off in an all-or-none fashion through structural transition; transcriptional activities are activated/inhibited when a DNA molecule is in a coiled/compact state [22][23][24]. For a simpler phenomenological treatment of the activity level of transcription of DNA, we assume that the free energy function FðgÞ depends on this order parameter g and that it has two minima as shown in Fig.…”
Section: Microscopic Fluctuating Dynamics Of Genetic Products Togethementioning
confidence: 97%
“…(23) or Eq. (24b) that the statistical properties of the noise term on the environmental factor f can be expressed by…”
Section: Microscopic Fluctuating Dynamics Of Genetic Products Togethementioning
confidence: 98%